Indicadores de qualidade na formação corporativa: gestão de EaD no Tribunal Regional do Trabalho da 2ª Região - Alves, José Marcos (2018)
The distance education modality (EaD) has gained increasing importance in work environments for the continuous training of professionals; however, it weighs on the EaD a stigma of being considered a modality of low quality. In the Brazilian Judiciary, the EaD is responsible for the initial and continuous training of magistrates and servants. Therefore, the present research aims at identifying the quality indicators used to guide and understand the excellence in the production and supply of distance courses in work environments. For which we analyzed the offer of the course Introduction to Socio-Environmental Issues, produced by the Judicial School of the Regional Labor Court of the 2nd Region (EJUD2). For this challenge, the following questions were raised regarding the research problem: What are the guidelines that guide the design and the implementation of EaD in Brazil and EJUD2? What are the quality benchmarks for the distance modality, based on the national guidelines and academic productions in the area? What is the importance and contribution of Instructional Design in the design of courses offered in EaD, especially in EJUD2? Among the evidenced quality indicators, which ones are applied in the courses offered in EAD at EJUD2 and, consequently, are responsible for the excellence pointed out by the students of these courses? In this context, the general objective was to identify and analyze such indicators in order to understand the excellence of the online course under consideration. As for the specific objectives, they aimed to: i. To raise the history and guidelines that guide the design and implementation of Distance Education in Brazil, as well as in the judicial school of the Regional Labor Court of the 2nd Region - SP; ii. to understand the quality references for the distance modality, from the national guidelines and academic productions in the area; iii. to analyze the importance and the contribution of Instructional Design in the quality of the content design and courses offered in EaD; iv. indicate which are the quality indicators evidenced in the courses offered in EAD in EJUD2 responsible for excellence in results. The research adopted a qualitative exploratory approach to a case study. For this, the data of the student reaction evaluations, the tutor's report, and a questionnaire interview with a person in charge of the instructional designers team and with coordinator manager of the EJUD2 were analyzed. The theoretical framework used to base this research was centered on, among other authors: Behar (2009), Corrêa (2007), Freire (1996), Pierre Lèvy (2003), Andrea Filatro (2008), Gardner (1995), Terçariol (2016), in addition to the Quality Reference for Distance Higher Education, Distance Learning Manual within the scope of EJUD2 and also official documents of higher bodies that regulate EAD in the judiciary. The research identified the production of contents as a fundamental point in the quality of EaD. In addition, it has been verified that audiovisual content, inherent of the technological advances, a current and enriching language, that allows to work the ludic. It is believed that this research contributes to the studies focused on the valuation of EaD in work environments in order to assist in the delineation of new paradigms of quality of this emergent modality in Brazil.